Kronstadt Identifi cation via Spatial Allusions of the Past - D. V. Basova (Сравнительная политика, 2015)
As a matter of fact, Kronstadt is a unique space: geographically situated on the watershed between Russia and Europe, it mostly preserves “internal” orientation — in other words, aimed at its insulation, than external. Such historically formed space perception impacts the immunity of the bases of local identity among the citizens. Despite the loss of a forbidden city status in 1996, the features of isolatedness and peculiarity are still typical for Kronstadt. It is possible to follow these characteristics on the level of written sources, which clearly demonstrate the markers of this city’s «uniqueness».